Histopathological description of Pseudophallus (supernumerary penis) - Tarik Ibrahem, Ali; Ahmed Ghazi, Faisal; Omar Emad, Ibrahim; Ahmed G., Alattraqchi (2013)
A case of congenital anomaly diagnosed in 19 years male penis. The condition is an extremely rare incident when presented as a case of supernumerary penis (diphallus) not a companied with other anomalies related to other systems or organs. However, to the authors knowledge, searching through the literature provides no information on histopathological description for such anomaly. Accordingly, this rare interesting case is evaluated through histopathological assessment in a trial to diagnose the tissue changes and origin.